2008
DOI: 10.1002/macp.200800332
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Behavior of Poly(ε‐caprolactone) Grafted onto Cellulose Alkyl Esters: Effects of Copolymer Composition and Intercomponent Miscibility

Abstract: Graft copolymers of CA and CB with PCL were prepared at compositions rich in PCL. Kinetic DSC data were analyzed in terms of a folded‐chain crystallization formula expanded for a binary mixing system of amorphous/crystalline polymers. The order of crystallization rates was plain PCL > CA‐g‐PCL (DS = 2.98) > CB‐g‐PCL (DS = 2.1–2.95) > CA‐g‐PCL (DS = 2.1–2.5), and the fold‐surface free energy of the PCL crystals obeyed the reverse order. POM revealed a generally tardy growth of spherulites for all the graft copo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 32 publications
(88 reference statements)
5
25
0
Order By: Relevance
“…The methods of synthesis and characterization of CA-g-PCLs and CB-g-PCLs have been described in our previous study [5].…”
Section: Ca-g-pcl and Cb-g-pcl Copolymersmentioning
confidence: 99%
See 1 more Smart Citation
“…The methods of synthesis and characterization of CA-g-PCLs and CB-g-PCLs have been described in our previous study [5].…”
Section: Ca-g-pcl and Cb-g-pcl Copolymersmentioning
confidence: 99%
“…Recently, the authors' group has synthesized graft copolymers of CA and cellulose butyrate (CB) of acyl DS > 2 with poly(-caprolactone) (PCL), the products being termed CA-g-PCL and CB-g-PCL, respectively [5]; the two trunk CEs (CA and CB) are, respectively, immiscible and miscible with PCL in the corresponding binary polymer blends [5,6]. In that study [5] using copolymer compositions rich in PCL content, it was shown that all the products except copolymers based on CA of DS > 2.9 indicated an obviously single T g in differential scanning calorimetry (DSC) measurements, but the melt-crystallization kinetics of the PCL component and resulting supramolecular morphology were largely different in the manner of the composition dependence between the two graft series. In a subsequent work [7], we investigated enzymatic hydrolysis behavior of PCL for melt-molded films of the above CE-g-PCLs by employing Pseudomonas lipase and demonstrated that the degradation rate and the surface morphology of the films were both subtly changeable by adequate selections of the compositional parameters and intercomponent miscibility of the original copolymer products.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the authors have carried out systematic works for synthesizing biodegradable cellulose estergraft-aliphatic polyesters, through adoption of a homogeneous reaction system and complete removal of a possible oligomeric by-product of the grafting component (Teramoto and Nishio 2003;Teramoto et al 2004;Nishio 2006). Various approaches in this regard have dealt with chemical composition and thermal transition behaviour (Teramoto and Nishio 2003;Teramoto et al 2004), mechanical properties (Teramoto and Nishio 2003), higher-order structure development (Teramoto and Nishio 2004b;Kusumi et al 2008), and enzymatic hydrolysis behaviour (Teramoto and Nishio 2004a;Kusumi et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Chemical modification of cellulosics makes it easier for processing, but attention should be paid to the respect that their original biodegradability is lost in some cases. A remedy for overcoming such problems could be improvement of thermal moldability of cellulosics by grafting1–5 or blending1, 6–12 with biodegradable aliphatic polyeters.…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that cellulose butyrate of n = 4 and cellulose valerate of n = 5 exhibit the highest miscibility on blending with PCL. However, biodegradable13, 14 and commodity‐type cellulose acetate (CA) of n = 2 was judged to be immiscible with PCL over the entire composition range, although a certain material modification using the CA‐PCL combination could be achieved by graft copolymerization 2, 4, 5…”
Section: Introductionmentioning
confidence: 99%